Feasibility and effectiveness of an online mindfulness meditation program for medical students - Danilewitz, Marlon; Koszycki, Diana; Maclean, Heather; Sanchez-Campos, Millaray; Gonsalves, Carol; Archibald, Douglas; Bradwejn, Jacques (Canadian Medical Education Journal, 2018)
Background: The need to incorporate tools to promote medical student wellness in medical education is underscored by the concerning rates of psychological distress among them. The objective of this prospective cohort study was to obtain preliminary data on the feasibility and effectiveness of an online mindfulness intervention for medical student wellness. Methods: A convenience sample of 52 medical students consented to participate in this study. Feasibility was assessed by ease of recruitment, number of modules completed, satisfaction with the program, and adherence to a regular meditation practice. Participants completed the Maslach Burnout Inventory, the Jefferson Scale of Empathy-medical student version, the Five Face of Mindfulness Questionnaire-short form, and the Self Compassion Scale-short form pre and post intervention. Results: The convenience sample was recruited within a two-month period. Forty-five participants completed at least one of seven modules. Descriptive statistics (mean±standard deviation) revealed that the mean number of modules completed was 4.85±2.7. Mean satisfaction with the modules was 7.07±1.1 out of 10. Adherence to a regular formal meditation practice was poor; the average amount of formal meditation practice per module was 34.14±27.44 minutes. Self-compassion and the “observe and describe” facets of mindfulness practice significantly statistically increased from baseline, but no such change was observed for levels of burnout and empathy. Conclusion: The present study indicates that an online mindfulness meditation program may be of interest to medical students. The results did not provide any evidence that the program was effective but we believe further research and development is warranted.